The Geopolitical Vision of the State of Chile towards its Border Projection in the ’Great North’: Some Critical Readings - Ovando, Cristian; Álvarez, Gonzalo; López, Sophie (Geopolítica(s). Revista de estudios sobre espacio y poder, 2020)
Classic geopolitical knowledge has been a key approach to analysing Chile’s Great Northern Region border problems. On this issue, continuities, changes and nuances in theoretical area have been disclosed such as, for instance, the dialogue with International Relations approaches (say, with ideas related to the realist paradigm). In the policies field, it is noted that new perspectives have been introduced which differ from traditional geopolitics, although the latter still exert an important influence on various aspects of defence policy, foreign policy and national policies. Therefore, both dimensions – renewed and traditional – coexist in the definition of Chile’s State policies and institutions towards the Great North and the border. The problematization carried out in this article is informed by critical geopolitics ideas. The analysis, in sum, focuses on the presence of “renewed and traditional” perspectives in the practical approximation of Chile towards the Great North border.